NeuroSymbolic Safety Routing for Explainable Scientific Foundation Models under Uncertain Knowledge Conditions - Jiangyi Yin (Computational Intelligence Systems, 2026)
The increasing deployment of large-scale scientific foundation models in high-stakes domains such as climate modeling, drug discovery, and autonomous systems demands rigorous safety mechanisms that can operate under epistemic uncertainty. Purely statistical or purely symbolic approaches each exhibit fundamental limitations in such contexts: neural models lack interpretability and robustness to distributional shifts, while symbolic systems struggle with scalability and data-driven pattern recognition. This paper proposes a neurosymbolic safety routing framework that integrates deep learning architectures with structured logical reasoning to achieve explainable and reliable guidance for scientific foundation models. The framework operates by constructing a layered control architecture in which a neural perception module extracts latent features from uncertain inputs, a symbolic reasoner enforces domain-specific constraints, and a routing mechanism dynamically selects the most trustworthy inference path based on uncertainty quantification. We examine structural trade-offs across dimensions of computational overhead, representational fidelity, and explainability, showing that the proposed approach outperforms both purely neural and purely symbolic baselines in benchmarks involving adversarial perturbations and missing data conditions. The paper further addresses governance challenges, including the need for audit trails, fairness across underrepresented scientific subdomains, and policy implications for certification of AI systems in critical infrastructure. Through cross-domain case illustrations in climate ensembles and molecular property prediction, we demonstrate that neurosymbolic safety routing provides a scalable and transparent foundation for deploying scientific foundation models under uncertain knowledge conditions without sacrificing performance or accountability.